2016
DOI: 10.1080/0142159x.2017.1270429
|View full text |Cite
|
Sign up to set email alerts
|

Developing a competency framework for academic physicians

Abstract: The framework developed represents a step towards closing the gap between the skills medical students are taught and the skills required of academic physicians. The model was customized to the context of the current organization and included a future orientation and addressed the literature calling for increasing focus on the administrative skills of academic physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In addition to their potential benefits for well‐being, studies have suggested that MBIs could facilitate doctors’ performance in relation to doctors’ activities in providing patient care . In providing patient care, mindful doctors may be more likely to perform better in interpersonal domains: they are trained to have a non‐judgemental attitude towards thoughts and feelings, and therefore may more openly listen and empathically respond to patients’ worries and emotions .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their potential benefits for well‐being, studies have suggested that MBIs could facilitate doctors’ performance in relation to doctors’ activities in providing patient care . In providing patient care, mindful doctors may be more likely to perform better in interpersonal domains: they are trained to have a non‐judgemental attitude towards thoughts and feelings, and therefore may more openly listen and empathically respond to patients’ worries and emotions .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, clinical core competences, including clinical skills and patient care, mastery of medical knowledge, health promotion and disease prevention, information and management, professionalism, interpersonal communication, academic research, and teamwork have become key to de ning medical staff's ability worldwide [24][25][26]. High clinicians' competency scores have become measures of good clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Section three asked the participant to rank 10 qualities from most important to least important from a provided list. We created this 10-item list in conjunction with a medical librarian and an expert in medical education by reviewing literature pertaining to CRs, academic medicine, and general leadership, generating an initial list of 71 qualities we thought might be important in a CR [2][3][4][5][6][7][8][9][10][11][12][13]. Then, we iteratively categorized, batched, and narrowed the terms to a list of 10 items that were widely represented in the literature, represented a broad range of quality types, and were felt to be important by all team members.…”
Section: Survey Development and Distributionmentioning
confidence: 99%